UNCOVERING WORKPLACE DYNAMICS FROM THEIR IMPACT ON JOB SATISFACTION - Lestari, Nadia Indri; Firdasari, Aulia Vivi; Oktaviyanti, Ika (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The relationship between job satisfaction at PT Otsuka Indonesia Distribution, workplace conflict, job stress, and salary was examined in this study. Method: The study used a quantitative methodology and data from 101 employees. Results: Job satisfaction was positively affected by workplace conflict and job stress, but salary had a beneficial effect. Remuneration had a beneficial effect but had a negative impact on job satisfaction. Novelty: All of these elements have an impact on job satisfaction, which emphasizes how important it is to address workplace dynamics for organizational success.